2018
DOI: 10.1029/2018gl077607
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Vertical Distribution of Rainfall‐Induced Strain Changes in a Landslide Measured by Distributed Fiber Optic Sensing With Rayleigh Backscattering

Abstract: Distributed fiber optic sensing with Rayleigh backscattering, which has been recognized as a novel technique for measuring differences in temperature or strain, was adopted in a borehole to a depth of 16 m in an actual landslide to detect a vertical profile of strain changes. Strain changes were measured every with a spatial resolution of 10 cm and strain resolution of 1.87 με. The measurements provided a clear-cut vertical profile of the strain changes caused by rainfalls that cannot be detected by convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…In this case, DFOS technology is increasingly in demand in the oil and gas industry and is deemed as an ideal sensing solution to detect fluid migration and evolution in situ to benefit from its electromagnetic interference (EMI) immunity, long‐lasting durability, installation ease, and small physical footprint when compared with that of traditional electrical sensing and foil strain gauge. Among various DFOS technologies, Brillouin optical time‐domain reflectometry (BOTDR), optical time‐domain reflectometry (OTDR), and optical frequency domain reflectometry are frequently used to simultaneously measure parameters including strain, temperature, and pressure along the entire fiber length (Kogure & Okuda, ; Luca Schenato, ). Both are superior to other optical sensors, such as quasi‐distributed fiber Bragg grating (FBG) that is used for local measurement and Raman‐based distributed temperature sensing (DTS) that is used only for temperature (Arnon et al, ; Sun et al, ; Sun et al, ;Sun et al, ; Tyler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, DFOS technology is increasingly in demand in the oil and gas industry and is deemed as an ideal sensing solution to detect fluid migration and evolution in situ to benefit from its electromagnetic interference (EMI) immunity, long‐lasting durability, installation ease, and small physical footprint when compared with that of traditional electrical sensing and foil strain gauge. Among various DFOS technologies, Brillouin optical time‐domain reflectometry (BOTDR), optical time‐domain reflectometry (OTDR), and optical frequency domain reflectometry are frequently used to simultaneously measure parameters including strain, temperature, and pressure along the entire fiber length (Kogure & Okuda, ; Luca Schenato, ). Both are superior to other optical sensors, such as quasi‐distributed fiber Bragg grating (FBG) that is used for local measurement and Raman‐based distributed temperature sensing (DTS) that is used only for temperature (Arnon et al, ; Sun et al, ; Sun et al, ;Sun et al, ; Tyler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed a near-surface zone at approximately 0-to 6-m depth where the Brillouin frequency shift fluctuated markedly over time ( Figure S8b), which was primarily attributed to the variation of shallow soil temperature (Bense & Kooi, 2004;Kogure & Okuda, 2018). This can be readily addressed by employing an additional FO temperature cable insensitive to mechanical strains (Habel & Krebber, 2011;Schenato, 2017).…”
Section: Resultsmentioning
confidence: 80%
“…Previous research showed vertically distributed strain sensing of a shallow landslide up to ~15 m (Kogure & Okuda, ). In their study, the measured strains were not converted to actual deformation, probably due to the complicated correlation between axial linear strain and shear deformation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite lack of standardized backfilling procedure, current practice indicates that FO borehole backfilling materials are of similar stiffness as surrounding strata and so E b and μ b are considered to be within 0.01–40 GPa (Plinninger et al, 2010) and 0.15–0.45, respectively. The radius of borehole, r b , is assumed to range from 25 to 200 mm (Kogure & Okuda, 2018; Zhang et al, 2018), and the ground‐borehole interface adhesion coefficient, k b , from 1 to 1,000 GPa/m (Xiang & Wang, 2018).…”
Section: Parametric Analysismentioning
confidence: 99%